Effect of Annealing and Artificial Ageing Parameters on The Ultimate Tensile Strength and Elongation of New Al-(4-5) Zn- Mg-Mn-Cu Alloys Fabricated using Recycled Beverage Cans - Badarulzaman, Nur Azam; Kazeem, Abubakar; Job Ajala, Amkpa; Faiz Wan Ali, Wan Fahmin; Emmanuel, Okorie Maduako (International Journal of Integrated Engineering, 2020)
The transport industry is one of the highest consumers of aluminium alloys. However, the quest for new and cheaper aluminium with properties comparable to the contenders has remain in the research domain for sometimes. Even at that, the literature is dearth of clear ideas on conversion of the huge RBCs to X7475 experimental alloys. In furtherance to the fabrication of a new 7xxx (Al-4-5Zn-1.5Mg-1.0Mn-0.35Cu) alloy from Recycled Beverage Cans (RBCs), the effect of annealing temperature (350 oC, 380 oC and 413 oC) and artificial ageing time (6, 10.5 and 15 hours) on the ultimate tensile strength (UTS) and elongation (e) were reported. Nine samples (S1-S9) of experimental alloys were fabricated and subjected to tensile tests, SEM/EDX and XRD analysis. Secondary phases like MgZn2, Cu2Mg precipitates as observed in the XRD supported an improved UTS. The elemental analysis revealed the presence of alloying compositions. An alloy fabricated using Al-5Zn-1.5Mg-1.0Mn-0.35Cu (S9), artificially aged at 6 h and annealed at 413 oC had the highest UTS of 362.2 MPa and an elongation of 3.09 mm (15.45 %). The result demonstrated that a new X7475 alloy was fabricated from RBCs with comparable mechanical properties with alloys fabricated using pure aluminium.